Teachers' perspectives on picture books themed on disasters for early childhood - Ratna Dwi Nurcahyani; Azhar, Aghnia Farrassyania; Musfita, Regita; Rizkita, Diantifani (IKIP Siliwangi, 2024)
In this study, the author discusses teachers' perspectives on illustrated storybooks in introducing disaster preparedness to young children. This research employed a descriptive design. The objective of this study is to provide a detailed or systematic description of teachers' perspectives on the development of illustrated storybook learning media with a disaster theme to be introduced to young children, The data collection technique used by the author is an interview with a Focus Group Discussion (FGD) approach. The analysis technique used is by transcribing the results of interviews conducted with experts in detail. A transcript is a process of transferring data from audio recordings or field notes into a descriptive text. The research results can serve as a basis for researchers in developing illustrated storybooks on disaster themes for young children.